Unprecedented 2020 coral bleaching reveals unexpected taxa-specific responses in the central Red Sea - Natalie Dunn; Fabio Marchese; Catherine S. McFadden; Laura Macrina; Marta Ezeta Watts; Megan K. B. Nolan; Francesca Giovenzana; Francesca Benzoni (PLoS ONE, 2025)
Sea surface temperature of the Red Sea has increased by up to 0.45 °C per decade over the last 30 years, and coral bleaching events are becoming more frequent. A reef bleaching event was observed in October 2020, whereby some parts of the Red Sea experienced more than 12 °C-weeks. The study sites spanned nearly three degrees of latitude along the central Saudi Arabian Red Sea and were surveyed via structure-from-motion photogrammetry in October 2020 during the bleaching event and again in October 2022 to track the fate of the coral colonies. The in situ temperatures in 2020 ranged from 31.9 °C to 32.7 °C, and overall, 65% of the colonies exhibited some bleaching. Nearly half of the colonies exhibited partial or complete mortality in 2022, although 18% exhibited complete mortality. Approximately 27% of the colonies presented no visible change in coloration over the study period, whereas 21% presented recovery over the two years. Porites, Montipora, Pocillopora, and Stylophora were classified as winners, whereas Acropora, Goniastrea, Xeniidae, and Sclerophytum were classified as losers. At the time of this study, this research was the first to assess the longest-term changes in coral colonies following a major reef bleaching event in the central Saudi Arabian Red Sea. The results suggest that the 2020 bleaching event may be the most severe event on record for the region at the time of the study, and our data underscore the need for enhanced monitoring of corals and environmental data to better understand coral reef ecosystem resilience in a historically data scarce region.